2013
DOI: 10.1071/an13207
|View full text |Cite
|
Sign up to set email alerts
|

Use of partial mixed rations in pasture-based dairying in temperate regions of Australia

Abstract: There is a growing diversity and complexity of dairy farming systems in Australia. Feeding systems based on the provision of mixed rations to dairy cows grazing perennial pastures (termed partial mixed rations or PMR systems) have emerged and present the dairy industry with opportunities for improved production and feed efficiency, but also with significant challenges. Early research results are beginning to define the situations in which PMR systems are profitable and the mechanisms responsible for the improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…These results are in agreement with the available information on the advantages of the system in confinement, where cows consuming TMR diet produce more milk than cows grazing or in mixed systems, which is associated with an increase in DMI and greater availability of energy (Bargo et al, 2002;Fajardo et al, 2015;Kay, Mackle, & Auldist, 2002;Kolver & Muller, 1998;Meikle, Adrien, Mattiauda, & Chilibroste, 2013;Vibart, Fellner, Burns, Huntington, & Green, 2008;Wales et al, 2013). In addition, the change from a mixed system to a single system in confinement with TMR improved the production and composition of milk in a short period of time, evidenced from one week before the change to one week after.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are in agreement with the available information on the advantages of the system in confinement, where cows consuming TMR diet produce more milk than cows grazing or in mixed systems, which is associated with an increase in DMI and greater availability of energy (Bargo et al, 2002;Fajardo et al, 2015;Kay, Mackle, & Auldist, 2002;Kolver & Muller, 1998;Meikle, Adrien, Mattiauda, & Chilibroste, 2013;Vibart, Fellner, Burns, Huntington, & Green, 2008;Wales et al, 2013). In addition, the change from a mixed system to a single system in confinement with TMR improved the production and composition of milk in a short period of time, evidenced from one week before the change to one week after.…”
Section: Discussionsupporting
confidence: 88%
“…For example, in summer, high environmental temperatures and humidity (heat stress) affects the production and milk composition, health and reproduction (Bernabucci et al, 2010(Bernabucci et al, , 2015Cowley, Barber, Houlihan, & Poppi, 2015;Jordan, 2003). Thus, due to the fluctuation in the availability of forage that occurs at different times of the year (Bargo, Muller, Delahoy, & Cassidy, 2002;Chilibroste, Soca, Mattiauda, Bentancur, & Robinson, 2007;Wales et al, 2013) and adverse weather conditions (heat stress), confinement system with access to shade is used as an alternative management in dairy cattle to reduce the negative effects on milk production and improve animal welfare (Charlton & Rutter, 2017;Schütz et al, 2010;). In this sense, total mixed ration (TMR) has been strategically incorporated to increase total dry matter (DMI) and energy intake to ensure an adequate balanced supply of nutrients in quality and quantity throughout the year.…”
mentioning
confidence: 99%
“…The milk production of cows that received supplementation with a partial TMR in pasture-based systems was increased compared with that of cows that consumed solely a pasture diet (O'Neill et al, 2012;Miguel et al, 2014). Further per-cow advantages have also been found during periods of low pasture accumulation rate or in areas with low grazing availability (Wales et al, 2013). Additionally, a mixed diet, including grazed pasture + partial TMR, improved the DMI and milk production of high-producing dairy cows compared with supplementation with concentrate (Bargo et al, 2002).…”
Section: Introductionmentioning
confidence: 86%
“…Although this decrease could accompany the normal decline in the lactation curve around the peak of milk production [17], as it was only observed in Post-TMR cows, it was probably associated to a restriction in DMI and/or increased in energy requirements after the change of the diet [6]. It has been reported that not only characteristics of the pasture, but also its management can limit DMI of grazing animals [4] [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, the quantity and quality of the pasture offered is variable throughout the year, determining an imbalance between nutrient supply and demand at various stages of the production cycle of the modern dairy cow [2]. Thus, the inclusion of concentrates and silages in the dairy cow diet has increased to meet the requirement of the milking herd [3] [4]. In this regard, the use of a total mixed ration (TMR) in early lactation allows dairy cows achieve maximum performance in times of reduced pasture dry matter (DM) production, determining an increase in milk yield, cow body condition score (BCS), metabolic status and reproductive performance [5] [6] [7].…”
Section: Introductionmentioning
confidence: 99%